The higher levels of self-reported satisfaction, the lower risk of depressive symptoms: Evidence from a nationwide cross-sectional study in China - Niu, Zhiping; Zhao, Feng; Wen, Weihong; Han, Donghui; Zhang, Keying; Zhao, Xiaolong; Han, Shichao; Yang, Fa; Duan, Zhizhou; Qin, Weijun (Frontiers in Medicine, 2022)
Objectives: To investigate the associations between several dimensions of self reported satisfaction and the risk of depressive symptoms among Chinese middle-aged and older adults. Methods: A nationwide cross-sectional study of middle-aged and older adults was conducted from the China Health and Retirement Longitudinal Study (CHARLS). Depressive status was evaluated using the 10-item center for epidemiological studies depression scale (CESD-10) and self-reported life, health, marital status, parent-child relationship, and air quality satisfaction were adopted using Likert 5-point evaluation methods. Generalized linear model (GLM) was applied to explore the association between satisfaction and depression risk. Results: A total of 13,978 Chinese people aged over 45 years old were included in this study and 35.7% of the participants had depressive symptoms. GLM analysis indicated that all dimensions of satisfaction were negatively associated with the risk of depressive symptoms. For each 1-point increase in life, health, marital status, parent-child relationship, and air quality satisfaction, the incidence of depressive symptoms decreased by 60.8% (odds ratio (OR) = 0.392; 95% confidence interval (CI): 0.370, 0.414), 56.3% (OR = 0.437; 95% CI: 0.418, 0.458), 41.8% (OR = 0.582; 95% CI: 0.555, 0.610), 37.2% (OR = 0.628; 95% CI: 0.596, 0.662), and 25.6% (OR = 0.744; 95% CI: 0.711, 0.778), respectively. Conclusion: Higher levels of satisfaction with life, health, marital status, parent-child relationship, and air quality are associated with lower risk of depressive symptoms among middle-aged and older adults. Given the aging society and the increasing mental health problems of middle-aged and older adults in China, our study provides a comprehensive perspective for depression prevention and mental health improvement.